2017
DOI: 10.1097/sla.0000000000001804
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes for Mastectomy Patients Receiving Neoadjuvant Chemotherapy

Abstract: Objective:To evaluate the risk of neoadjuvant chemotherapy for surgical morbidity after mastectomy with or without reconstruction using 1:1 matching.Background:Postoperative surgical complications remain a potentially preventable event for breast cancer patients undergoing mastectomy. Neoadjuvant chemotherapy is among variables identified as contributory to risk, but it has not been rigorously evaluated as a principal causal influence.Methods:Data from American College of Surgeons National Surgical Quality Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
1
12
2
Order By: Relevance
“…This can be explained by the multi-centre nature of our series with initially less experience in OBC techniques. Interestingly, we found a significantly lower overall complication rate after neo-adjuvant chemotherapy (15.9%) despite others reporting no difference in complication rates after neo-adjuvant chemotherapy followed by OBC or mastectomy 4,39 .…”
Section: Discussioncontrasting
confidence: 67%
“…This can be explained by the multi-centre nature of our series with initially less experience in OBC techniques. Interestingly, we found a significantly lower overall complication rate after neo-adjuvant chemotherapy (15.9%) despite others reporting no difference in complication rates after neo-adjuvant chemotherapy followed by OBC or mastectomy 4,39 .…”
Section: Discussioncontrasting
confidence: 67%
“…The overall complication rate in the present study was higher than that observed in Ibadan by Ogundiran et al, [2] and Bowen et al [10] in which complications were limited to 30 days postoperative period so did not include late complications such as recurrence andupper limb oedema but similar to the report of N"guessam et al [5] As at the time of this report, 41.6% of the patients were alive having been followed up for at least six months, while 39% were lost to follow-up care and 19.4% were dead. This pattern is similar to the experience of others.…”
Section: Neoadjuvantcontrasting
confidence: 74%
“…chemotherapy had been associated with postoperative wound complications of mastectomy in the past but recent studies showed no increase in postoperative morbidity. [9,10] In the present study, 31% had neoadjuvant chemotherapy and half of them had a postoperative complication.…”
Section: Neoadjuvantmentioning
confidence: 47%
“…The rates of short‐term complications in our patients were similar to those reported in this study. Other reports have similarly shown acceptable complication rates of immediate breast reconstruction after NAC, even when radiation therapy is also utilized . In terms of oncologic outcomes, Prabhu et al showed that IR may delay time to post‐mastectomy radiation in patients treated with neo‐adjuvant chemotherapy, but that there were no differences in locoregional control, disease‐specific survival, and overall survival when compared to a cohort of patients who did not have breast reconstruction .…”
Section: Discussionmentioning
confidence: 99%